Ehlers-Danlos Syndrome and Narcolepsy: An Incidental Relationship? - Lindsay, Miliken; Karim, Sedky (Journal of Sleep And Sleep Disorder Research, 2019)
Ehlers Danlos syndrome (EDS) is a collagenic disease that has often been associated with different types of sleep disorders ranging from insomnia to obstructive sleep apnea (OSA). EDS usually has associated fatigue and excessive daytime sleepiness (ES), thus narcolepsy should be excluded as a cause. Literature review suggests a high prevalence of hypersomnia disorders in this population. We present two sporadic cases presenting with typical symptoms of narcolepsy.